Struktur Anatomi Kayu Kecapi (Sandoricum koetjape Merr) - Muthmainnah, Muthmainnah (Universitas Tadulako, 2019)
Kecapi wood (Sandoricum koetjape Merr) is one type of wood from community forest, including in the family Meliaceae and which as types the lesser known wood. Completeness of data on the types the lesser known wood will open up better opportunities for the prospects of the wood utilization. This paper studies the anatomical properties and its fiber quality of Kecapi wood. The anatomical structure were examined according to the IAWA List of microscopic features, while fiber qualities were examined based on its quality for pulp and paper. The result showed that Kecapi wood : heartwood is yellow browish, fine-medium texture, straight grain. The main anatomical characteristics weregrowth ring indistinct,diffuse porous, diagonal or radial porous distribution,vessel solitary and in radial multiples of 2-4 cells, vessel size is small and rather small, parenchyma vascicentric. Aliform-konfluen,rays width 1-3 cells and until 4 cells. Fiber length, diameter and wall thickness were 1128 30.19 and 3.87 µm. Fiber quality of Kecapi wood were classified into quality class II